Current knowledge on the prevalence and detection techniques of Clonorchis sinensis in China - Zhang, Jianming; Cao, Jian; Cao, Liang; Zhang, Chao; Gong, Liyuan; Kang, Xiaohong (Frontiers in Veterinary Science, 2025)
BackgroundClonorchis sinensis is one of the most significant zoonotic food-borne parasites, particularly prevalent in China. The adult form of C. sinensis typically inhabits in the hepatic and biliary tracts of various mammals, including humans, and is considered a major contributor to the incidence of cholangiocarcinoma. The life cycle of C. sinensis is complex, understanding its prevalence among different host species is essential for developing prevention and management measures. Furthermore, the clinical manifestations of clonorchiasis are often overlooked or misdiagnosed. Therefore, the development of early detection methodologies will facilitate timely treatment and reduce associated complications.MethodsThe current review was conducted in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A comprehensive search for relevant articles was performed across PubMed, Web of Science, Google Scholar, China National Knowledge Infrastructure, Wanfang, and Wipro databases. The selected studies investigated the prevalence of C. sinensis among various host species in China, and developed the corresponding diagnostic approaches.ResultsVarious diagnostic approaches have been established for detecting C. sinensis. These methods encompass direct identification, molecular techniques, serological assays, and imaging modalities, each of which targets distinct aspects such as morphological characteristics, DNA sequences, specific antibodies, and the visual representation of C. sinensis. The prevalence characteristics of C. sinensis across different host species have been examined in China, with the majority of studies concentrating on the second intermediate hosts, specifically fishes, and the definitive hosts, namely humans. The overall prevalence of C. sinensis among fish species was found to be 18.36% (4,892/26,646, 95% CI 17.90–18.82), with notably high detection rates observed in the provinces of Heilongjiang, Qinghai, Liaoning, and Shandong. In Chinese human population, the average detection rate of this pathogen was recorded at 3.98% (60,306/1,513,994, 95% CI 3.95–4.01), with the highest rates occurring in the provinces of Jiangxi, Hunan, Guangdong, and Heilongjiang Provinces.ConclusionThis review emphasized on the widespread prevalence of C. sinensis among different host species in China, and summarized the existing diagnosis methods developed in China. These findings will establish a foundational framework for the prevention, control, and potential eradication of clonorchiasis in China.